2018
DOI: 10.1177/0022466918807464
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Mediated Joint Attention Intervention in the Preschool Classroom

Abstract: Children with autism spectrum disorder (ASD) and other developmental disabilities are at risk of isolation from same-aged peers. Furthermore, research indicates that even in inclusive settings, children with ASD benefit from targeted interventions and support. Among the social communication skills that are frequently absent in children with ASD is joint attention. Joint attention can be defined as shared engagement between two individuals on a third object or event and has been identified as potential pivotal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Nearly a half of the studies (n = 16) was conducted in school (e.g., Barton, 2015;Charlop & Greenberg, 2009;Hansen et al, 2019), five at home (e.g., Armendariz & Hahs, 2019), two in both home and class (Cannella-Malone et al, 2010;Van Der Meer et al, 2013). Similarly, Shepley et al (2019) found that most of 123 studies were conducted in school settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nearly a half of the studies (n = 16) was conducted in school (e.g., Barton, 2015;Charlop & Greenberg, 2009;Hansen et al, 2019), five at home (e.g., Armendariz & Hahs, 2019), two in both home and class (Cannella-Malone et al, 2010;Van Der Meer et al, 2013). Similarly, Shepley et al (2019) found that most of 123 studies were conducted in school settings.…”
Section: Discussionmentioning
confidence: 99%
“…In 23 of the studies reviewed, the implementer was the researcher (e.g., Schaefer-Whitby et al, 2019) while a teacher implemented the procedure in four (e.g., Kern et al, 2007). A master student and an occupational therapist (Lund & Troha, 2008), a teacher assistant (Xin & Leonard, 2015), a peer (Thiemann-Bourque et al, 2016), both a peer and the researcher (Hansen et al, 2019) were also among the implementers. Parents were the implementers in three studies (Erturk et al, 2020;Hansen et al, 2018;Raulston et al, 2019), and mother and researcher in one study (Van Der Meer et al, 2013).…”
Section: Implementermentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Joint Attention, Symbolic Play, and Emotional Regulation (JASPER) uses environmental arrangement, prompting, and child-led play to improve joint attention and social engagement (Chang, Shire, Shih, Gelfand, & Kasari, 2016). Further research has used other packages of supported practices, including social narratives to prompt prosocial behavior prior to play (e.g., Hansen et al, 2018), visual supports to plan play (Charlop, Lang, & Rispoli, 2018), and activity-based intervention that capitalizes on natural learning opportunities (e.g., Barton, Choi, & Mauldin, 2019). Parents of children with ASD have been trained and coached to implement social-communication interventions using didactic trainings, role-play, prompting, and performance feedback methods (Ruppert, Machalicek, Hansen, Raulston, & Frantz, 2016).…”
mentioning
confidence: 99%